Akuntansi Manajemen Limbah Industri Perhotelan (Studi kasus: Sebuah Hotel Bintang Empat di Makassar) - Surahmah Kurnia; Syamsinar Syamsinar; Afdaliah Afdaliah (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2020)
The purpose of this research is to produce the accounting information for management decision making about the estimation of revenue and cost of waste cultivation in hotel. The research methodology used descriptive quantitative using waste material exchange and recycle as the alternatives waste cultivation. The empirical result shows that the estimation of financial performance (profit) which sourced from solid and liquid waste cultivation based on the parameter used will be consideration and recommendation